The impact of undergraduate nursing students’ time management disposition on innovative behavior: the chain mediating role of academic self-efficacy and flow experience - Lin, Ye; Wang, Xixi; Zhang, Xinyi; Hu, Hongli; Liu, Li; Pang, Keyi; Li, Yan; Hu, Chaoqun; Sun, Zhiqin; Li, Xiaona (Frontiers in Psychology, 2025)
ObjectiveTo explore the chain intermediary effect of academic self-efficacy and flow experience of undergraduate nursing students in the influence mechanism of time management disposition on innovative behavior.MethodsSeven hundred and sixty-three undergraduate nursing students from 3 universities in Jiangsu Province were investigated with Adolescent time Management Disposition Scale, Academic Self-efficacy Scale, Flow Short Scale and Innovation Behavior Scale. The chain intermediary model was constructed and verified.ResultsThe time management disposition of undergraduate nursing students was positively correlated with their average scores in academic self-efficacy, flow experience, and innovative behavior. The direct impact of time management disposition on innovative behavior was significant, and academic self-efficacy and flow experience exhibited both independent mediating effects and a chain mediating effect.ConclusionThe time management disposition of undergraduate nursing students can significantly positively predict innovative behavior, in which academic self-efficacy and flow experience play a significant independent intermediary role and chain intermediary role. Nursing teachers and students can promote innovative behavior from the point of view of improving time management skills, enhancing academic self-efficacy and flow experience.